RHETORICAL DIMENSIONS OF KALAM KHABARI (INFORMATIVE SPEECH) AND KALAM INSYA’I (PERFORMATIVE SPEECH) IN THE QUR'AN AND THEIR IMPLICATIONS FOR EDUCATIONAL VALUES - zabila Refania; Ferki Ahmad Marlion; Wulan Kurnia; Ilda Amanda (UIN Maulana Malik Ibrahim Malang, 2026)
This study aims to analyze the forms and rhetorical functions of Kalam Khabari and Kalam Insya’i in Surah An-Nazi‘at from the perspective of Arabic rhetoric (balaghah), particularly within the framework of ʿIlm al-Maʿani. This research employs a qualitative approach using a library research method. The primary data source is the Al-Qur’an, specifically Surah An-Nazi‘at, while secondary data are derived from classical tafsir works, authoritative references on Arabic rhetoric, and relevant academic literature. Data were collected through documentation by identifying and classifying the verses into categories of Kalam Khabari, including Khabar Ibtida’i, Khabar Thalabi, and Khabar Inkari, as well as Kalam Insya’i, which comprises non-requestive (ghairu thalabi) forms such as oath (qasam) and requestive (thalabi) forms including interrogative (istifham) and imperative (amr). The data were analyzed using a descriptive-analytical method to explain their linguistic structures, rhetorical functions, and educational values. The findings reveal that Surah An-Nazi‘at is predominantly composed of Kalam Khabari, particularly Khabar Ibtida’i, which functions to convey fundamental theological messages concerning resurrection and divine authority. Meanwhile, Kalam Insya’i serves as a rhetorical medium for emphasis, reflection, admonition, and moral instruction. The integration of these two forms demonstrates a Qur’anic rhetorical strategy that combines informative discourse with transformative educational impact.Keywords: Kalam Khabari; Kalam Insya’i; ʿIlm al-Maʿani